Modelling and optimisation of train electric drive system based on fuzzy predictive control in urban rail transit. (2016) - Huang, Yeran; Cao, Fang; Ke, Bwo-ren; Tang, Tao
This paper establishes an elaborate model of train electric drive system to simulate the train operation process. The transmission loss and train length are taken into account when calculating voltage of contact line and resistance force with equivalent slope. Considering the influence of voltage and slope variation on control performance, we propose original model original control with fixed voltage (OMOC-FV) and original model original control with slope (OMOC-S) to compare with the most commonly used PI control method, i.e., modified model original control (MMOC). Moreover, focusing on variable parameters and complex dynamics of induction motor, a fuzzy predictive control method, called modified model modified control (MMMC), is proposed to track the target speed profile accurately and to achieve the voltage stability. The effectiveness of elaborate model and the performance of MMMC are evaluated based on the data of Beijing Yizhuang line.